OCCURRENCE OF BACTERIAL CANKER OF TOMATO IN HIMACHAL PRADESH, INDIA: IDENTIFICATION AND MOLECULAR CHARACTERIZATION OF THE PATHOGEN - GURVINDER SINGH; NARENDER K. BHARAT; MONICA SHARMA (The Bioscan, 2015)
Bacterial canker disease was widespread in all the tomato growing localities surveyed in Himachal Pradesh, India with an incidence and severity of 30.10 and 23.68 per cent, respectively. The disease symptoms appeared on stem, leaves, fruits and buds of infected tomato plants. Young plants showed poor growth and wilting. On older leaves dark brown spots appeared with yellow halo at leaf edges. Bird’s eye spots appeared on fruits as brown, raised and surrounded by a persistent white halo. The bacterial colonies appeared as creamish to yellow in colour, roundish and semi fluidal on nutrient agar. Bacterium was identified to be Clavibacter michiganensis subsp. michiganensis on the basis of morphological characters, physiological and biochemical tests as well as pathogenicity tests. After molecular characterization of five isolates through direct polymerase chain reaction (PCR) with C. michiganensis specific primer pair CMR 16F1/R1 and nested PCR with C. michiganensis specific primer pair CMR 16F2/R2, the identity of three isolates viz., Cmm 1, Cmm 2 and Cmm 3 was confirmed to be Clavibacter michiganensis ssp. michiganensis. This is the first confirmed report on the bacterial canker in the tomato growing areas of Himachal Pradesh, India. The present investigation has firmly indicated the appearance of the disease in main tomato growing belt of the state.